Development of Value Added Products From Home-Grown Lychee (Journal of Environmental Science and Natural Resources, 2015)
The experiment was concerned with developing of home-grown Lychee based different products, like squash and jelly to assess its prospect in respect to its marketability and food value. The fruits were collected from the local market and the pulp was extracted. Then the pulp was analyzed for proximate composition. The proximate analysis of lychee pulp showed 78.2% moisture, 17-18% TSS, 6.68% reducing sugar, 6.89% non-reducing sugar, 13.75% total sugar, 0.69% ash, 4.92 pH, 0.327% acidity and 1.2 mg/100gm vitamin C. Products were stored at room temperatures (28°C) and changes during storage were observed at an interval of 30 days for a period of 6 months. A testing panel consisting 10 panelists studied the acceptability of the samples. The consumers preferences were measured by statistical analysis of the scores obtained from the response of the panel. Among the samples the following sample of squash, jelly was awarded the highest scores by the panelists; S-2 respectively.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22159 J. Environ. Sci. & Natural Resources, 7(1): 121-125 2014